2018
DOI: 10.4028/www.scientific.net/msf.925.36
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Crystal Growth Theory of Graphite in Cast Iron

Abstract: The problem of graphite crystallization and growth in cast iron has recently received increased attention. As most of the published literature describe analysis of room temperature graphite, there is a legitimate concern that the crystallization of graphite is concealed by recrystallization and growth in solid state occurring after solidification. To avoid confusion in the interpretation of room temperature graphite morphology, the authors used Field Emission Gun SEM on deep-etched interrupted solidification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The structure of the surface layer of graphite separations observed in the surface of the contraction cavity suggests that this is a primary graphite that crystallizes in a metal liquid, which is confirmed by authors in the papers [25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 64%
“…The structure of the surface layer of graphite separations observed in the surface of the contraction cavity suggests that this is a primary graphite that crystallizes in a metal liquid, which is confirmed by authors in the papers [25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 64%
“…An interesting phenomenon was captured in Figure 3 , which showed that besides bifilm inclusions, the contraction cavities also contained spheroidal graphite precipitates. The external surface of the graphite precipitates suggests that these are primary precipitates [ 16 , 17 , 18 , 19 ]. These precipitates were pushed out of the liquid alloy towards the contraction cavity.…”
Section: Resultsmentioning
confidence: 99%
“…There has been some interest in separating graphite from kish as a value‐added coproduct, however, the high levels of impurities, particularly silica, make processing and purification costly [34] . Nickel, cobalt, and magnesium are additional metals that have demonstrated, similar to iron, the ability to incorporate, or dissolve, carbon, creating a metal‐carbide that precipitates graphite in the molten phase (1200–1400 °C) [35–37] . Metal‐catalyzed graphite grows in the vertical c‐axis to a greater extent than mineral graphite, which typically favors the lateral α ${\alpha }$ ‐axis [26,27,38] .…”
Section: Graphite Production Via Catalytic Graphitizationmentioning
confidence: 99%
“…[34] Nickel, cobalt, and magnesium are additional metals that have demonstrated, similar to iron, the ability to incorporate, or dissolve, carbon, creating a metal-carbide that precipitates graphite in the molten phase (1200-1400 °C). [35][36][37] Metal-catalyzed graphite grows in the vertical c-axis to a greater extent than mineral graphite, which typically favors the lateral a-axis. [26,27,38] Thus, the morphologies of metal catalyzed graphite typically consist of crystallites with high dimension ratios of vertical stacking (L c ) to horizontal expansion (L a ) (Figure 5), making them suitable for lithium-ion intercalation and deintercalation.…”
Section: Graphite Production Via Catalytic Graphitizationmentioning
confidence: 99%